Device therapies for heart failure with reduced ejection fraction: a new era - Mody, Rohit; Nee Sheth, Abha Bajaj; Dash, Debabrata; Mody, Bhavya; Agrawal, Ankit; Monga, Inderjeet Singh; Rastogi, Lakshay; Munjal, Amit (Frontiers in Cardiovascular Medicine, 2024)
Even with significant advancements in the treatment modalities for patients with Heart Failure (HF), the rates of morbidity and mortality associated with HF are still high. Various therapeutic interventions, including cardiac resynchronization therapy, implantable cardiovascular-defibrillators (ICDs), and Left Ventricular Assist Devices (LVADs), are used for HF management. Currently, more research and developments are required to identify different treatment modalities to reduce hospitalization rates and improve the Quality of Life (QOL) of patients with HF. In relation to this, various nonvalvular catheter-based therapies have been recently developed for managing chronic HF. These devices target the pathophysiological processes involved in HF development including neurohumoral activation, congestion, and left ventricular remodeling. The present review article aimed to discuss the major transcatheter devices used in managing chronic HF. The rationale and current clinical developmental stages of these interventions will also be addressed in this review.